Humans vs. artificial intelligence - MacCarald, Clara, 1979- (Artificial intelligence (Focus Readers (Firm)), 2020)
Briefly explores the history of artificial intelligence and compares and contrasts human intelligence and ability with AI abilities--such as AI programmed to play games like "Jeopardy!" and able to beat human players. Includes a glossary.